NATURAL RESEARCHES AND MATHEMATICAL MODELS OF SUBURBAN PASSENGER TRANSPORTATION - Мироненко, В. К.; Габа, В. В.; Мацюк, В. І.; Грушевська, Т. М.; Костюшко, В. П. (Science-based technologies, 2014)
In the article analyzed approach commuter passengers to platform, filling of trains on a specific direction, based on which received regularities the approach of passengers to platform, the rate of filling and habitability commuter train. The obtained results enable to carry out calculations of important technical and technological parameters suburban of transportations of passengers such as intervals between the departure of trains, habitability carriages in commuter trains, the definition of a number of turnstiles at the appropriate number of passengers, the safety on the platform, enhancing the convenience and comfort of passengers. Been developed the mathematical model the approach of commuter passengers to platform for any passenger flow and interval between trains. This model allows you to quickly and easily calculate passenger flow in any period of time and assess filling of train by passengers at a specified time t. Constructed a universal analytical model that can describe the filling of platform by passengers for any habitability train and interval between trains, that is very important for the organization of process of transportation of passengers.